General and oral health status of preterm one-year-old very low and extremely low birthweight infants (a cross - sectional study) - Merglová, Vlasta; Hauer, Lukáš; Broukal, Zdeněk; Dort, Jiří; Koberová Ivančaková, Romana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
AIMS: The aim of the present study was to evaluate the general and oral health status of a group of preterm one-year-old very low (VLBW) and extremely low birthweight (ELBW) infants and make a comparison with full-term one-year-old normal birthweight infants (NBW). METHODS: A cross-sectional study was conducted in 102 one-year-old preterm VLBW and ELBW infants, and the data obtained were compared to 87 one-year-old full-term NBW infants. The infants' medical histories were obtained from hospital records and interviews with the mothers. The oral cavities of all infants were examined under the same conditions. The chi-square test, Pearson's chi-square test of independence and Mann-Whitney test were used for the statistical evaluation, with P < 0.05 considered statistically significant. Relative risk (RR) and 95% confidence interval (CI) estimates for variables significantly associated with oral findings were calculated. RESULTS: Both perinatal variables (gestational age, mode of delivery, birthweight, Apgar score, resuscitation, orotracheal intubation and presence of intraoral pathology) and neonatal variables (antibiotic treatment and infections) had a significant association with prematurity, VLBW and ELBW. The one-year-old preterm VLBW and ELBW infants frequently suffered from general diseases, frequently received regular medication and had fewer erupted primary teeth; they also had a higher prevalence of developmental defects of the enamel and deformations of the hard palate. CONCLUSION: This study confirmed anamnestic, medical and oral differences between one-year-old preterm VLBW and ELBW and full-term NBW infants.
Keywords: Infant, Very Low Birth Weight; Cross-Sectional Studies; porodní hmotnost; gestační stáří; Infant; Gestational Age; Pregnancy; těhotenství; orální zdraví; novorozenec; Oral Health; lidé; ženské pohlaví; Humans; Birth Weight; Infant, Newborn; kojenec; průřezové studie; novorozenec s velmi nízkou porodní hmotností; Female